Limitless Worker Surveillance - Ajunwa, Ifeoma; Crawford, Kate; Schultz, Jason (California Law Review, 2016)
From the Pinkerton private detectives of the 1850s, to the closed-circuit cameras and email monitoring of the 1990s, to contemporary apps that quantify the productivity of workers, American employers have increasingly sought to track the activities of their employees. Along with economic and technological limits, the law has always been presumed as a constraint on these surveillance activities. Recently, technological advancements in several fields – data analytics, communications capture, mobile device design, DNA testing, and biometrics – have dramatically expanded capacities for worker surveillance both on and off the job. At the same time, the cost of many forms of surveillance has dropped significantly, while new technologies make the surveillance of workers even more convenient and accessible. This leaves the law as the last meaningful avenue to delineate boundaries for worker surveillance. In this Article, we examine the effectiveness of the law as a check on worker surveillance, given recent technological innovations. In particular, we focus on two popular trends in worker tracking – productivity apps and worker wellness programs – to argue that current legal constraints are insufficient and may leave American workers at the mercy of 24/7 employer monitoring. We then propose a new comprehensive framework for worker privacy protections that should withstand current and future trends.